2014
DOI: 10.1111/cas.12494
|View full text |Cite
|
Sign up to set email alerts
|

Ampelopsin‐induced autophagy protects breast cancer cells from apoptosis through Akt‐mTOR pathway via endoplasmic reticulum stress

Abstract: Our previous study has shown that ampelopsin (AMP), a flavonol mainly found in Ampelopsis grossedentata, could induce cell death in human breast cancer cells via reactive oxygen species generation and endoplasmic reticulum (ER) stress pathway. Here, we examined whether autophagy is activated in AMP-treated breast cancer cells and, if so, sought to find the exact role and underlying molecular profile of autophagy in AMP-induced cell death. Our results showed that AMP treatment activated autophagy in MDA-MB-231 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 43 publications
(115 reference statements)
2
59
0
2
Order By: Relevance
“…47 To determine whether Linc00152 contributes to chemoresistance through activating the AKT pathway, the specific AKT signaling inhibitor MK2206 and activator IGF-1 were used in the research, respectively. 48,49 Consistent with the speculation, increased cell response to L-OHP was observed when AKT signaling pathway was blocked in Linc00152-overexpressing cells. On the other hand, activation of the AKT signaling pathway decreased the sensitivity of cells to L-OHP induced apoptosis in 1 5 9 13 17 21 25 29 33 37 41 45 49 53 57 61 65 69 73 77 81 85 89 93 97 101 105 109 113 117 121 125 129 These results demonstrated that Linc00152 contributed to L-OHP resistance at least in part through modulating the miR-193a-3p/ ERBB4/AKT axis.…”
Section: Discussionsupporting
confidence: 69%
“…47 To determine whether Linc00152 contributes to chemoresistance through activating the AKT pathway, the specific AKT signaling inhibitor MK2206 and activator IGF-1 were used in the research, respectively. 48,49 Consistent with the speculation, increased cell response to L-OHP was observed when AKT signaling pathway was blocked in Linc00152-overexpressing cells. On the other hand, activation of the AKT signaling pathway decreased the sensitivity of cells to L-OHP induced apoptosis in 1 5 9 13 17 21 25 29 33 37 41 45 49 53 57 61 65 69 73 77 81 85 89 93 97 101 105 109 113 117 121 125 129 These results demonstrated that Linc00152 contributed to L-OHP resistance at least in part through modulating the miR-193a-3p/ ERBB4/AKT axis.…”
Section: Discussionsupporting
confidence: 69%
“…with 80 mg/kg of quercetin twice a week; 30 mg/kg 3MA twice a week; a combination of 30 mg/kg 3 MA and 80 mg/kg of quercetin twice a week; or a vehicle control injected with the same volume of saline for 4 weeks [78]. The results of this study are consistent with the trend of predecessor studies [56,60,77] showing that quercetin has the potential to induce protective autophagy in cancer cells through AKT-mTOR and hypoxia-induced factor 1α signaling [79,80] and in this way to induce autophagy in ovarian cancer cells [81].…”
Section: Chemoprotective Activities In Ovarian Cancer Cells Of Quercesupporting
confidence: 84%
“…20 The major pathway of ER stress is unfolded protein response (UPR), which is identified to recover ER homeostasis and promote cell survival. 21 In addition, ER stress has proved to be one of the inducers of autophagy. 22 Interestingly, DHA induced-ER stress has been observed in several tumor cells, 23,24 and our previous studies have demonstrated that DHA both induce apoptosis and autophagy in various cancer cells.…”
Section: Introductionmentioning
confidence: 99%